2022
DOI: 10.1088/1361-6528/ac8e0a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of folic acid-conjugated chitosan-coated PLGA nanoparticles for targeted delivery of Peganum harmala smoke extract to breast cancer cells

Abstract: In this study, PLGA-NPs coated with folic acid-chitosan (PCF-NPs) loaded with Peganum harmala smoke extract (PSE) were synthesized (PSE-PCF-NPs), and their anti-cancer effects were evaluated. PSE-PCF-NPs were synthesized by the nanoprecipitation method and then characterized by DLS, SEM, and FTIR methods. HPLC and UV–vis spectroscopy were used to evaluate the PSE’s folic acid (FA) binding and encapsulation. PSE-PCF-NPs-mediated cell viability and apoptosis were investigated by MTT, qPCR, flow cytometry, AO/PI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Moreover, the results showed that ARC‐PCF‐NPs have a remarkable inhibitory effect on Gram‐positive bacteria. Similarly, a study with the synthesis of PLGA NPs coated with CS and FA containing Peganum harmala smoke extract found that these NPs scavenge ABTS and DPPH free radicals, decrease ferrous in FRAP test, increase intracellular reactive oxygen species, and decrease the expression of SOD gene in breast cancer cells 29 . In addition, Alirezaei et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the results showed that ARC‐PCF‐NPs have a remarkable inhibitory effect on Gram‐positive bacteria. Similarly, a study with the synthesis of PLGA NPs coated with CS and FA containing Peganum harmala smoke extract found that these NPs scavenge ABTS and DPPH free radicals, decrease ferrous in FRAP test, increase intracellular reactive oxygen species, and decrease the expression of SOD gene in breast cancer cells 29 . In addition, Alirezaei et al.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a study with the synthesis of PLGA NPs coated with CS and FA containing Peganum harmala smoke extract found that these NPs scavenge ABTS and DPPH free radicals, decrease ferrous in FRAP test, increase intracellular reactive oxygen species, and decrease the expression of SOD gene in breast cancer cells. 29 In addition, Alirezaei et al used PLGA-based NPs modified with CS-FA in order to optimize the antitumor effects of Dermina vulgaris essential oil. They found that these NPs increase apoptosis and inhibit the angiogenesis of HT-29 cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, there is no significant difference in fluorescence between the coated and uncoated nanoparticle treatments on the PC-3 cell line ( Figure 9 (B1,B2)) and Table 5 . This suggests a greater selective uptake of the coated nanoparticles by the PSMA-positive LnCap cell line compared with the PSMA-negative PC-3 cell line, which could be facilitated by the binding of the PSMA receptors on the LnCap cells by the folic acid moieties on the surface of the coated nanoparticles, allowing them to enter the cells by receptor-mediated endocytosis [ 52 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%